(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Agro-industry in DIY contributes to the economy in terms of the contribution of its product exports, where of the 16 commodities exported, 11 of them are dominated by agricultural processing product. This research aims to find out (1) what the structure-conduct-performance (SCP) of agro-industry in DIY in 2016, (2) which agro-industry sector was leading in DIY in 2016, and (3) compare the suitability between DIY government policies and the results of the analysis. This research uses an input-output method where forward and backward linkages are used to measure structure, output and income multipliers to measure conduct, and the degree of export dependence and export multipliers on output to measure performance. The research results show that DIY’s leading agro-industry sector is the food and beverage supply sector because it has high forward and backward linkages, high output and income multipliers, as well as high degrees of export dependence and export multipliers on output. This is in line with the publication from the Bappeda DIY regarding the Final Report on Preparing Analysis of the Impact of Infrastructure on DIY’s Economic Development in 2016 which stated that the food and beverage supply sector was included in the leading sectors in DIY in 2016.